The leadership habit transforming behaviors to drive results - Berberick, Tammy R.; Lindsay, Peter; Fritchen, Katie (Ascent Audio, 2024)
The Leadership Habit provides the framework for patterns of behavior that will transform the way you lead. By articulating a clear, well-defined standard of what it means to be a leader, this book condenses volumes of advice and opinion into ten key areas and teaches leaders how they can create daily habits surrounding these centers of excellence. Leaders who can commit to creating change will develop more productive teams and will build long-term growth for their organization. This book is your invaluable guide to being one of the greats, with proven advice and a concrete framework for leading well. Through expert discussion and deep dissection of these critical areas, you'll discover how to drive for results, build the best team, execute on vision, foster innovation, and more. As a leader, your team's performance and your organization's outlook are direct reflections of you. Discover how to become a catalyst for driving performance and results by transforming your actions every day.
Online resource; title from title details screen (O'Reilly, viewed September 10, 2024)
Keywords: Leadership; Audiobooks; Livres audio